Effect of Pellet Diameter in Broiler Prestarter Diets on Subsequent Performance - Cerrate, S.; Wang, Z.; Coto, C.; Yan, F.; Waldroup, P. W. (International Journal of Poultry Science, 2008)
Different size pellet dies and two levels of dietary energy density were used in prestarter broiler diets formulated to meet typical commercial standards. In the first experiment, birds reared in battery brooders were offered diets containing either 0.5 or 2.5% poultry oil from 0 to 14 days. Each group of diets was assigned different feed forms such as mash continuously through the study or mash, pellet diameters of 1.59, 2.38 and 3.17 mm dies or crumbled diets from 0-7 days followed by crumbled diets to 14 days and pelleted diets to 35 days. In the second experiment, birds reared in floor litter were assigned the same treatments as the previous study except the 2 levels of poultry oil were supplied from 0-42 days of age. During the first seven days birds fed the 1.59 and 2.38 mm diameter die or crumble diets had higher body weight than did birds fed the other feed forms; however, this positive effect was dissipated as the birds grew older. The feed intake kept almost the same tendency as the body weight. The feed conversion at 7 days was improved as pellet size was reduced. It is thought that this was due in large part to better nutritive value since, birds fed crumbled and pelleted diets have almost the same feed intake but different feed conversion. Birds given the mash feed during the whole period had lower body intake and feed intake than those birds fed other feed forms. The body weights and feed conversions at 35 and 42 days were improved as the level of poultry oil increased. Improvement in feed conversion by birds fed diets with 2.38 and 3.17 mm diameter die or crumble diets at 7 days and mash or 3.17 mm diameter die diets at 42 days was observed as the dietary energy level increased. These data indicate that pellet diameters of 1.59 or 2.38 mm can be beneficial during the prestarter period and can be more useful with 2.5% poultry oil.